2002
DOI: 10.1081/pdt-120002230
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Benzoic Acid, Sorbic Acid, Benzyl Alcohol, and Benzalkonium Chloride by Flexible Tubing

Abstract: Earlier studies using methylparaben, propylparaben, and several types of flexible tubing showed that the parabens are sorbed by a number of commonly used tubing. The sorption increased with increase in time of contact and the tubing surface area. The temperature and pH ranges tested did not affect sorption. Current studies evaluated other commonly used antimicrobial preservatives used in oral, parenteral, opthalmic, nasal, and other pharmaceutical products. These preservatives include benzoic acid, sorbic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…These results were expected based on earlier reported studies using several different 10 ft lengths of tubing with these and other commonly used preservatives. [3,4] …”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…These results were expected based on earlier reported studies using several different 10 ft lengths of tubing with these and other commonly used preservatives. [3,4] …”
Section: Resultsmentioning
confidence: 98%
“…[3,4] These earlier studies used 10 ft lengths of silicone, PVC, Teflon w , and other types of commonly used flexible tubing. Results showed that no sorption occurred with Teflon tubing while rapid losses were noted with silicone and PVC tubing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several new structural elements appeared to be necessary during the analysis (Lužar, 2005). Results appeared in different patterns, therefore three subcategories were formed: Rd (direct results): Report results, obtained in the study, presented in the paper [e.g., “As the depth profiling proceeded, the chlorine signal increased and the relative intensity of the phosphorous decreased” (Felton & Perry, 2002)]. Rn (indicated results): Do not report results, but only indicate the kind of results that can be expected in the paper [e.g., “A guide for stabilization of pharmaceuticals to oxidation is presented” (Waterman et al, 2002)]. Rp (previous results): Report results, obtained from a published study [e.g., “Earlier studies using methylparaben, propylparaben, and several types of flexible tubing showed that the parabens are sorbed by a number of commonly used tubing” (Bahal & Romansky, 2002)]. …”
Section: Methodsmentioning
confidence: 99%
“…Rp (previous results): Report results, obtained from a published study [e.g., “Earlier studies using methylparaben, propylparaben, and several types of flexible tubing showed that the parabens are sorbed by a number of commonly used tubing” (Bahal & Romansky, 2002)].…”
Section: Methodsmentioning
confidence: 99%